Analiza kwalifikacji kadry inżynierskiej i menedżerskiej w regionie łódzkim na podstawie badania ankietowego - Szmit, Anna; Stanieć, Iwona; Żółtowski, Jan (Qualification of Engineers and Managers' in Lodz Region Based on the Results of the Questionnaire Audit, 2008)
The qualification of the employees' competences is a multidimensional problem. The proper graduate's preparation is not easy, because of the changeability of the employers' requirements and also because of the market needs. That is why it is necessary to undertake the effort to recognize the needs of the changing market, which makes it easy to adjust the profiles of the education to them. The analysis of the questionnaire audit's results is presented in this paper. The audit was conducted among Lodz voivodeship employers. The analysis was made from the point of view of the significance of employers' requirements in the relation to graduates. The cluster analysis and multidimensional scaling were used in the analysis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 144-151